Optimizing Marketing Strategies in Encouraging the Adoption of Mobile-Based Digital Financial Services among Students - Tri Yunarni, Baiq Reinelda; K. Tobing, Diana Sulianti; Iswanto, Dedy (Universitas Pendidikan Nasional, 2025)
This study analyzes effective marketing strategies to enhance the adoption of mobile application-based financial services among university students, particularly in Indonesia, where mobile banking and e-wallet penetration is high among the youth. The primary aim of this study is to identify and optimize marketing strategies that drive the adoption of digital financial services. Using a Systematic Literature Review (SLR) approach and PRISMA 2020 guidelines, this research analyzes 30 relevant peer-reviewed articles. The synthesis identifies key factors that promote and hinder the adoption of digital financial services. Key findings indicate that digital marketing strategies, particularly through social media, influencer marketing, and personalized content, are effective in increasing students' intention to adopt financial applications. Adoption factors include ease of use, perceived financial benefits, trust in data security, and digital financial literacy. However, major barriers remain, such as low financial literacy and distrust in data security. This research extends TAM and UTAUT models by highlighting the role of modern marketing strategies as external variables influencing adoption. Practically, the study emphasizes the need for integrated education-communication strategies and transparent trust-building mechanisms to enhance adoption. It also recommends focusing on financial literacy education and improving data privacy features to foster broader acceptance among student populations.